MiR-17-92 cluster dysregulation in lymphoid malignancies: Its role in lymphomagenesis - Roisman, Alejandro (2017)
MicroRNAs (miRNAs) are short, endogenous singled-stranded noncoding RNAs whose dysregulation has been implicated in important biologic processes, including cancer development. The principal mechanism of action of these master regulators is to control gene expression by suppressing mRNA translation and reducing mRNA stability. In particular, the miR-17-92 cluster is the most frequently miRNA expressed in different subtypes of non-Hodgkin lymphomas. Its widespread dysregulation in these pathologies suggests this cluster as a new biomarker that may supplement lymphoma diagnosis and prognosis, and also as an attractive target to design novel strategies for cancer therapy.